A case study on year round fodder production scheme for smallholder dairy producers in Bangladesh (Bangladesh Journal of Livestock Research, 2020)
This study was undertaken to develop a year round fodder production model for small scale dairy farmers. Five pregnant dairy cows of Red Chittagong Cattle (RCC) genotype were selected. For rearing five cows, 66 decimal of land was selected from existing fodder plots under Pachutia Research Farm at Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka. The selected land was divided into two parts (33 decimal in each). One part was brought under perennial (Napier-4 and Splendida) and the 2nd part of land for seasonal (Maize & Matikalai) fodder production. Data on live weight and live weight gain of cows, birth weight of calves, feed intake, milk production, actual biomass yield for both perennial and seasonal fodder, yearly manure production were recorded and calculated. Napier-4 grass, splendida, maize, straw, silage were supplied to the experimental cows according to the seasonal availability in different months. Concentrate mixture were also supplied consisting of wheat bran, kheshari (red gram), soybean meal, maize crushed, til oil cake, DCP and common salt. Economics of the model revealed that considering the sale of milk, calves and manure and cost included only feed and land leased, a farm/family rearing 5 indigenous dairy cows with his/her family labours, he/she could earn around BDT 98 thousand in a year (1$ = 85 BDT) and the benefit cost ratio of the model on total variable cost and total cost were 1.86 and 1.66, respectively. Therefore, it may be recommended that a farmer having 5 adult dairy cows with 66 decimal land under fodder cultivation may earn substantial share of his/her family income as small-scale rural dairying.Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 89-102